Development of learning models for inculcating Pancasila values - Taat Wulandari; Anik Widiastuti; Nasiwan Nasiwan; Johan Setiawan; Muhammad Rijal Fadli; Hadisaputra Hadisaputra (Institute of Advanced Engineering and Science, 2023)
The values contained in Pancasila have not been implemented in the life of the Indonesian people properly. This study aims to produce a product in the form of a model of planting Pancasila values. This research is a research and development, using a research and development model from Borg and Gall which is modified into seven development steps. Product validation of the Pancasila values inculcation model by learning technology experts and Pancasila education experts. Techniques data analysis used descriptive statistical analysis. This research resulted in a model named my real action plan for Pancasila (MRAPP). MRAPP is a learning model that can be used to inculcate Pancasila values. The steps of the MRAPP model are as: i) field observations; ii) determining one of the precepts of Pancasila; iii) designing real action; iv) making a schedule of activities and presentation of proposals; v) monitoring the implementation of real action; vi) reporting the process and results of real action; and vii) doing reflection. The results of the validation of the feasibility of the learning model from the validation of learning experts and the validation of Pancasila education experts, namely the MRAPP learning model declared “eligible” to be used as a learning model for inculcating Pancasila values.